Reputations and corporate malfeasance: collusive networks in financial statement fraud - Tillman, Robert H. (Crime, law and social change, 2009)
The prevailing theory used by economists to explain why more corporations do not engage in fraud focuses on the role of board members, auditors and banks in controlling corporate conduct and the "reputational penalties" that may be imposed on them if they fail to do so. In this view, beyond the formal sanctions imposed by criminal justice and regulatory agencies, these "control agents" are subject to extra-legal consequences for misconduct or failure to perform their duties in which their reputations for honesty and integrity are diminished and thus their value in the marketplace for their services declines. The "reputational penalty" theory has been challenged by recent work that asserts that these entities, far from controlling the behavior of corporate insiders, may form networks of "reputational intermediaries" who collude with corporate executives to give legitimacy to their illegal schemes. In this paper, empirical support for the latter view is provided through an analysis of a sample of 374 publicly traded firms that announced financial restatements between 1997 and 2002 and which were accused of securities fraud. The analysis shows that these schemes involved large numbers of board members, auditors, and bankers who aided and abetted senior managers in their attempts to deceive investors. These findings point to broader issues concerning: (1) the changing nature of corporate power; (2) the strengths of collusive networks; and (3) current policy debates regarding attempts to exert more regulatory control over corporate behavior.